2009
DOI: 10.1007/bf03191853
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers for population-genetic studies of shiitake (Lentinula edodes) strains

Abstract: In order to analyze the genotyping of shiitake Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Our results showed higher values for H E and PIC while the H O value was slightly lower compared to the results of the previous studies [23,24]. The five SSR markers developed by Kim et al [31] were reported to have H E of 0.58, H O of 0.38, and PIC value of 0.53 using cultivars from Korea, China, and Japan, as well as wild strains from Korea. Analysis of these markers showed H E of 0.53, H O of 0.38, and PIC value of 0.5 using 10 wild strains collected from Mt.…”
Section: Discussioncontrasting
confidence: 70%
“…Our results showed higher values for H E and PIC while the H O value was slightly lower compared to the results of the previous studies [23,24]. The five SSR markers developed by Kim et al [31] were reported to have H E of 0.58, H O of 0.38, and PIC value of 0.53 using cultivars from Korea, China, and Japan, as well as wild strains from Korea. Analysis of these markers showed H E of 0.53, H O of 0.38, and PIC value of 0.5 using 10 wild strains collected from Mt.…”
Section: Discussioncontrasting
confidence: 70%
“…In a wild population containing 88 Chinese L. edodes strains, the I and PIC values were 0.836 and 0.395, respectively (Xiang et al, 2016 ). In another study, the PIC value was 0.53 in 89 L. edodes strains from East Asia (Kim et al, 2009 ). Genetic variation of Chinese L. edodes cultivars is low and was postulated to be derived from a limited number of elite strains (Chiu et al, 1996 ).…”
Section: Discussionmentioning
confidence: 93%
“…Until recently, line typing and breeding of shiitake ( Lentinula edodes ) cultivars have been depended on traditional DNA markers like restriction fragment length polymorphism [ 20 ], randomly amplified polymorphism DNA [ 21 ], amplified fragment length polymorphism (AFLP) [ 4 ], and microsatellites [ 22 ]. However, these markers have limitations in that they often show low levels of reproducibility and usually lack specific genetic information (e.g., AFLP; genetic loci showing DNA polymorphisms are usually unknown).…”
mentioning
confidence: 99%
“…Kim et al . [ 22 ] used co-dominant microsatellite DNA markers (GenBank accession No. DQ231475~DQ231479) to discriminate 89 lines of shiitake from East Asia, including Korea, China, and Japan, but they found that precise cultivar typing was difficult because of insufficient genetic information.…”
mentioning
confidence: 99%
See 1 more Smart Citation